Pengembangan Modul Matematika Berbasis Accelerated Learning pada Materi Himpunan di SMPN 1 Kota Jambi - Nurul Fadila (Cahaya Ilmu Cendekia Publisher, 2021)
Pirpose of Study: The purpose of this research is to develop a mathematics module based on accelerated learning for material for class VII SMP which is valid according to experts and to determine the effectiveness of the module. Methodology: This type of research is development research using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The instruments used in this study were material validation assessment sheets, module design validation, questionnaires on product trials, student learning outcomes tests, student observation sheets, and student response questionnaires. Main findings: From the results of the analysis, the effectiveness of this module can be seen from the results of observations of student learning activities reaching 86.19% indicating the